2018
DOI: 10.1007/s13201-018-0859-7
|View full text |Cite
|
Sign up to set email alerts
|

Water quality evaluation using water quality index and multivariate methods, Beheshtabad River, Iran

Abstract: Rivers are critical to agriculture, industry, and the needs of humans and wildlife. This study evaluates the water quality of the Beheshtabad River in Iran's Chaharmahal and Bakhtiari Province, using water quality index and multivariate statistical methods. Nitrate, temperature, phosphate, turbidity, dissolved oxygen, biological oxygen demand, electrical conductivity, total solids, and pH were measured at five selected stations along the river over 6 months using standard methods. Water quality index results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 19 publications
2
26
0
5
Order By: Relevance
“…The extreme level of pollution may be due to various anthropogenic activities such as direct discharge of wastewater from surrounding households into the stream and deposition of various solid waste into the stream. Similar study by Fathi et al [35] reported that the WQI of the stream in the study increased from upstream to downstream.…”
Section: Discussionsupporting
confidence: 87%
“…The extreme level of pollution may be due to various anthropogenic activities such as direct discharge of wastewater from surrounding households into the stream and deposition of various solid waste into the stream. Similar study by Fathi et al [35] reported that the WQI of the stream in the study increased from upstream to downstream.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, water that is deemed fit for one purpose may be undesirable for another, as such an integrated approach which incorporates all the relevant chemical parameters of interest, usually guided by WHO [20], and local e Scientific World Journal drinking water standards in a particular groundwater system is relevant in characterising the suitability of water domestic for purpose. e water quality index (WQI) has been adopted by many studies for such purposes [48][49][50][51][52]. e same has been adopted in this study, the weighted arithmetic index approach modified after Brown et al [53], to assess the quality of groundwater for drinking purposes.…”
Section: Methodsmentioning
confidence: 99%
“…e most harmful pollution to the surface water bodies is due to the role of increasing contamination from industrial and urban wastewater along with the runoff from the agricultural land. e characteristics of the surface contaminations are considered as a nonpoint source, while industrial and municipal discharges are considered as a main point source due to the influenced responsibilities of water pollution [5][6][7]. Precipitations due to the climate change, surface flow, ground water flow, and the flow due to the pump are the major ones responsible for the discharge of the river along with the pollutant concentration on the surface water [5].…”
Section: Introductionmentioning
confidence: 99%